Main rotor aeroacoustic analysis & validation with test data and favorable planform design for minimal aerodynamic noise - Yücekayali, A.; Senipek, M.; Ortakaya, Y. (My University, 2015)
The main aim of this paper is to study the improvements or the deteriorations generated by blade planform modifications such as anhedral, taper, sweep, double sweep and their combinations on associated rotor characteristic which could not be straightforwardly evaluated with basic knowledge on aerodynamics, performance and aeroacoustic rule of thumbs. The physical mechanism behind the tradeoff between aeroacoustic, aerodynamic performance and rotor stall aspects is investigated and a better understanding for blade favorable planform shape design with low noise signature is developed. In this sense, blade planform modifications are performed on a base blade geometry and aeroacoustic, aerodynamic performance and stall onset characteristics are evaluated. Commercial tools such as Charm, PSU-WopWop and Camrad are utilized for comprehensive assessments. Aeroacoustic and aerodynamic analyses are validated with an experimental rotor whirl tower tests and HART-II test data. Various blade planforms are evaluated and the trade-offs between less noisy blade planforms with stall onset, power requirements, lag-wise and torsional moments are studied. Eventually, the drawbacks encountered in aerodynamic performance and rotor stall while designing blade planform for improved acoustic characteristics are investigated.
Keywords: Acoustics